Didactic Strategies in Special Graduate Projects - Doubront-Guerrero, Marcel Alejandro (2021)
This article is a reflection on how special graduate projects move away from the humanist context, promoting humanism, that is, a humanization of education without taking the human as a reference but the didactic strategies, ignoring who applies them and the factors involved in their application. In this sense, an approach is made referring not only to the purpose of education but also to Maslow’s theory of emotions in order to know, understand, and determine how and why teachers think, and also, what the most appropriate alternative should benefit education and its students.